The Influence Of Social Media On The Social Change Of The Deli Serdang Community - Risaleh Abie Yasir (Pena Cendekia Insani, 2021)
Along with the development of information technology so as to bring a change and influence in society itself. And with the birth of social media, it forms patterns of people's behavior and changes with the times, such as culture, norms, and ethics that are formed from childhood. Indonesia, including with a large population in various races, ethnicities, and religions, has a lot of potential for social change in society. There are no special restrictions for social media users, whether children, teenagers, or adults also use social media as a tool to convey or obtain information. So this research has the following problem formulation: what is the meaning of social media, what is the impact of social media on the people in North Sumatra, especially Kab. Deli Serdang and what is the influence of social media on social change in the people of North Sumatra, especially Kab. Deli Serdang. And the method in this study using descriptive research methods. Descriptive research is one type of research whose purpose is to present a complete picture and clarification of a social reality in society.